Analysis of the Deformation Law of Deep and Large Foundation Pits in Soft Soil Areas - Yang, Tao; Liu, Shuailei; Wang, Xueyan; Zhao, Hao; Liu, Yang; Li, Yanwei (Frontiers in Earth Science, 2022)
Taking a deep excavation in Suzhou soft soils adopting three support schemes as the background, the excavation performance metrics, including the heave and lateral deformation of diaphragm walls, surface vertical deformation, vertical deformation of surrounding buildings, and earth pressure, are thoroughly investigated based on 15 excavation cases collected in the soft soil area of Suzhou. Based on the analysis of monitoring data, some findings were achieved: the foundation pit deformation is greatly affected by the spatial effect. The existing station can constrain the foundation pit deformation. Benefiting from the combination of various support solutions, the average maximum deflection of the diaphragm wall is 0.10% He. The maximum lateral movement depth of the diaphragm wall (δhm) is mainly located at (He-7, He+12.5). The vertical deformation of the wall top is greatly affected by the excavation exposure time and soil conditions. The heave range of the wall top is (−0.08∼0.26%) He. Under the action of the displacement of the diaphragm wall to outside the pit and the upward displacement of the wall top, the ground surface is uplifted, and the maximum uplift is (0.02∼0.14%) He, ranging from 0.12δhm to 1.13δhm. The maximum surface settlement is (−0.01% ∼ −0.15%) He, ranging from −0.22δhm to −3.11δhm. The form of building heave is mainly affected by the surface heave and the distance from the diaphragm wall (d). When d is within a certain range, there is a heave settlement difference between the adjacent side and the opposite side of the excavation, and the adjacent side undergoes mostly subsidence, while the opposite side undergoes mostly uplift. The peak value of the apparent earth pressure (AEP) envelope is 0.59γHe, which falls within (0.47∼0.78) He. The calculation scheme proposed by Kim can be used to predict the AEP for multiple soil types.